Clinical and economic burden of prescribing tramadol and other opioids for patients with osteoarthritis in a commercially insured population in the United States. Issue 1 (5th January 2022) - Silverman, Stuart; Rice, J. Bradford; White, Alan G.; Beck, Craig G.; Robinson, Rebecca L.; Fernan, Catherine; Schepman, Patricia
Abstract : Use of tramadol and nontramadol opioids among patients with osteoarthritis is associated with increased rates of negative clinical outcomes, resource use, and costs. Abstract: In 2019, the American College of Rheumatology conditionally recommended tramadol and conditionally recommended against nontramadol opioids for patients with hip and knee osteoarthritis. Although tramadol is known to be less prone to opioid use disorders, little is known about the differing magnitude of negative clinical outcomes, health care resource utilization, and costs of tramadol relative to nontramadol opioids. Administrative claims records for commercially insured patients with osteoarthritis who were prescribed opioids were used to compare clinical and cost outcomes during a 3-year follow-up period by conducting a pre–post analysis and a matched case–cohort analysis. Data for 14, 491 patients were analyzed: 4048 (28%) were initiated on tramadol, and 10, 443 (72%) were initiated on nontramadol opioids. After matching, 4048 patients per cohort were analyzed. In each empirical analysis, tramadol patients did develop opioid use disorders; however, opioid use disorder rates were 3.5-fold higher in the nontramadol cohort (1.2% vs 4.2%). In addition, rates of other opioid-related clinical outcomes (falls, fractures, nausea, fatigue, and constipation) were also directionally lower among the tramadol cohort, although quantitatively similar (<5% difference) to the nontramadol cohort. Finally, in both analyses, the nontramadol cohort incurred higher levels of inpatient and emergency department visits and all-cause costs during the 3-year follow-up period. However, tramadol patients incur a higher incremental change (+$24, 013) in costs relative to their pretreatment baseline compared with nontramadol (+$18, 191). These real-world findings demonstrated lower risks with tramadol relative to other opioids, albeit risks and increased health care costs were present with tramadol, highlighting the need for further strategies to improve outcomes.